ICT in Teaching: An analysis of cases - Mirian Elisabet Almiron; Silvia Porro (Universidad Autónoma de Baja California, 2014)
Although increasingly, with ever more emphasis and frequency, the benefits of incorporating Information Technology and Communications (ICT) in teaching are touted, the reality is far from what is stated. In this paper the aim has been to investigate teachers' conceptions of ICT and how they apply them in the classroom. To this end, discourse analysis (DA) was performed on the opinions of three Natural Science teachers about the importance they assign to ICT, and the new challenges of education in today's society. The analysis results show that, although the discourse emphasizes the need for ICT in school, the reality is that teachers find it hard to implement them in the classroom.